2020
DOI: 10.1103/physrevb.101.115301
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the phonon mean free path spectrum in silicon membranes at different temperatures using arrays of nanoslits

Abstract: Knowledge of the phonon mean free path (MFP) holds the key to understanding the thermal properties of materials and nanostructures. Although several experiments measured the phonon MFP in bulk silicon, MFP spectra in thin membranes have not been directly measured experimentally yet. In this work, we experimentally probe the phonon MFP spectra in suspended silicon membranes. First, we measure the thermal conductivity of membranes with arrays of slits at different temperatures. Next, we develop a fully analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Phonons in Si have a maximum energy of the order of 50 meV, which means that a single electron with energies of a few eV can generate a large amount of phonons [28,29] as it travels between two metallic electrodes. At temperatures below 3 K phonons in Si have long mean free paths (up to 1 µm [30,31]) and even longer thermalization lengths. It is therefore expected that the emitted phonons reach the nanowire in an out-of-equilibrium state.…”
Section: Resultsmentioning
confidence: 99%
“…Phonons in Si have a maximum energy of the order of 50 meV, which means that a single electron with energies of a few eV can generate a large amount of phonons [28,29] as it travels between two metallic electrodes. At temperatures below 3 K phonons in Si have long mean free paths (up to 1 µm [30,31]) and even longer thermalization lengths. It is therefore expected that the emitted phonons reach the nanowire in an out-of-equilibrium state.…”
Section: Resultsmentioning
confidence: 99%
“…At temperatures below 3 K, phonons in Si have long mean free paths (up to 1 μm (refs. 32 , 33 )) and even longer thermalization lengths. It is, therefore, expected that the emitted phonons reach the nanowire in an out-of-equilibrium state 34 , 35 .…”
Section: Nature Of Generated Phononsmentioning
confidence: 99%
“…[ 22 ] The difference in thermal conductivity between crystalline and nanocrystalline silicon membranes therefore mainly stems from the scattering events at grain boundaries, whose frequency of occurrence in nc‐Si is directly linked to the grain size distribution. Furthermore, a recent experimental study on 145 nm‐thick crystalline Si membranes [ 41 ] shows that phonons with a mean free path above 215 nm contribute nearly 20% to thermal conductivity at room temperature. This proportion is expected to be relatively higher in our membranes due to the increased thickness and subsequent shift of the mean free path distribution towards higher values.…”
Section: Thermal Conductivity Measurements By µ‐Tdtrmentioning
confidence: 99%
“…Anufriev et al. [ 41 ] showed that phonon mean free path smaller than 400 nm contributes significantly to thermal conductivity in a 145 nm thick membrane. This suggests that the grain size distribution in our samples covers the range of mean free paths with the strongest contribution to thermal conductivity.…”
Section: Thermal Conductivity Measurements By µ‐Tdtrmentioning
confidence: 99%